Argument availability as a mediator of social theory perseverance - Anderson, Craig A.; New, B. Lynn
Research on belief perseverance-the finding that people cling to initial beliefs to an unwarranted extent-suggests that the availability of causal arguments plays an important mediational role. Specifically, a person's belief in a given domain may be a function of the relative availability of competing causal arguments in that domain. In an experiment testing this hypothesis of argument availability, subjects examined case history data suggestive of either a positive or negative relationship between a person's risk preference and ability as a firefighter. Half of the subjects were debriefed about the fictitious nature of the initial case history data. All subjects completed measures of their personal beliefs about this relationship, and then wrote out explanations of both of these competing social theories. Results indicated, as predicted, that (1)significant levels of perseverance occurred; (2) argument availability effects mirrored the perseverance effect; (3) within-cell correlations between argument availability and final social theories were significant; (4) based on a convariance analysis, argument availability did not account for all of the perseverance effect.